2007
DOI: 10.1002/jcb.21248
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme 2 is primarily epithelial and is developmentally regulated in the mouse lung

Abstract: Angiotensin converting enzyme (ACE) 2 is a carboxypeptidase that shares 42% amino acid homology with ACE. Little is known about the regulation or pattern of expression of ACE2 in the mouse lung, including its definitive cellular distribution or developmental changes. Based on Northern blot and RT-PCR data, we report two distinct transcripts of ACE2 in the mouse lung and kidney and describe a 5' exon 1a previously unidentified in the mouse. Western blots show multiple isoforms of ACE2, with predominance of a 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
73
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 45 publications
(85 reference statements)
7
73
2
Order By: Relevance
“…In the mouse lung, ACE-2 has been shown to be developmentally regulated, with mRNA highest at embryonic day 18.5, and to be expressed primarily in bronchiolar and alveolar epithelial cells [27]. In the human lung, airway epithelial cells are one of the first sites of contact by the SARS coronavirus during lung infection; moreover, ACE-2 has been shown to be the site to which the SARS virus binds to initiate tissue infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse lung, ACE-2 has been shown to be developmentally regulated, with mRNA highest at embryonic day 18.5, and to be expressed primarily in bronchiolar and alveolar epithelial cells [27]. In the human lung, airway epithelial cells are one of the first sites of contact by the SARS coronavirus during lung infection; moreover, ACE-2 has been shown to be the site to which the SARS virus binds to initiate tissue infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…8A) supports the theory that ACE-2 limits the accumulation of ANG II produced by AECs in response to bleomycin. Recent studies by Weiner et al (24) showed that AECs are the main source of lung tissue ACE-2 in the mouse. Whether or not the decrease in ACE-2 mRNA induced by bleomycin is mediated by autocrine production of ANG II (14) will be an interesting and compelling question for further study.…”
Section: Discussionmentioning
confidence: 99%
“…This observation forms the basis of our proposal: namely, that activation of endogenous ACE2 can affect the balance between the two axes and prevent vascular remodeling and pathological events that lead to PH. Additional evidence confirms that ACE2 is central to pulmonary endothelial function and lung pathophysiology: (1) ACE2 is abundantly expressed in the pulmonary endothelium (8)(9)(10)(11); (2) ACE2 is significantly decreased in lung biopsies of patients with idiopathic pulmonary fibrosis (9); (3) bleomycin-induced pulmonary fibrosis and PH are associated with a decrease in ACE2 activity (9); (4) patients with PH have an increase in circulating endothelial cells (CEC) (12) due to high pressure in the pulmonary circuits and increased shear stress in the pulmonary vasculature (13), and ACE levels in the CEC of PH are significantly higher (unpublished observation); (5) ACE2 knockout mice exhibited severe acute respiratory distress syndrome, which is attenuated with administration of recombinant ACE2 (14); (6) Ang II up-regulates ACE and down-regulates ACE2 in patients with hypertension (15); and (7) Higher ACE2 activity with increased angiotensin-(1-7) formation has been reported in heart ventricles of patients with primary PH (16), suggesting a cardiopulmonary protective role for ACE2 (17). Collectively, these observations led us to propose that activation of endogenous ACE2 could have a protective effect against PH.…”
mentioning
confidence: 83%